Herpetofauna Species Inventory in The Ngalau Tarang Area, Agam Regency, West Sumatera - Sumbari, Rafazen Sumbari; Nugraha, Fitra (Jurnal Serambi Biologi, 2023)
The purpose of this research is to find amphibians and reptiles that live in the Tarang Ngalau, Kamang Mudiak village, Kamang Magek sub-district, Agam Regency, West Sumatra. Because this area functions as a tourist attraction. Habitat changes will affect fauna at depth, especially herpetofauna, because herpetofauna are very sensitive to environmental changes. The method used is the Visual Encounter Survey (VES) by determining survey points in the Tarang Ngalau area for data collection. The data obtained is entered into the table of Anura and Reptile species by making the conservation status of the Anura and Reptile species found. The survey was conducted from December 2022 to January 2023. Based on the research conducted, an inventory of herpetofauna species in the Tarang Ngalau area found 4 amphibian species belonging to 4 families, namely: Dicroglossidae (1 species), Microhylidae (1 species), Ranidae (1 species), Bufonidae (1 species) and 4 species of reptiles belonging to 3 families namely: Colubridae (1 species), Gekkonidae (2 species) Colubridae (1 species).